2021
DOI: 10.3390/antibiotics10020101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antimicrobial Photodynamic Therapy on Organic Solution and Root Surface In Vitro

Abstract: Antimicrobial photodynamic therapy (a-PDT) is attracting attention as a new form of dental treatment. While it is primarily applied to produce an antibacterial effect, it decreases lipopolysaccharide (LPS) and protease activity. Here, we evaluated differences in the antibacterial activity of a-PDT on three types of bacteria and the effects on the organic substances (i.e., albumin and LPS). Furthermore, we investigated the effects of a-PDT on root surfaces. A FotoSan630® and toluidine blue were used to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
1
1
0
1
Order By: Relevance
“…A recent investigation pointed out that some PSs could interact with LPS, modify the structure of LPS, and alter the biological effects in cells, which may provide a different insight into the treatments not only in dentistry but also in general health (Couto et al, 2021). The result was in line with the findings of Matsushima et al (2021) who observed that aPDT treatment could lead to LPS decrease, organic resolution, organic debris removal, and root surface cleaning. Another study isolated inflamed human gingival fibroblasts (HGF) and treated them with MB plus light irradiation.…”
Section: Biofilm Growth/ Substratesupporting
confidence: 64%
“…A recent investigation pointed out that some PSs could interact with LPS, modify the structure of LPS, and alter the biological effects in cells, which may provide a different insight into the treatments not only in dentistry but also in general health (Couto et al, 2021). The result was in line with the findings of Matsushima et al (2021) who observed that aPDT treatment could lead to LPS decrease, organic resolution, organic debris removal, and root surface cleaning. Another study isolated inflamed human gingival fibroblasts (HGF) and treated them with MB plus light irradiation.…”
Section: Biofilm Growth/ Substratesupporting
confidence: 64%
“…Além dessas vantagens a Terapia Fotodinâmica é capaz de inativas as endotoxinas LPS (lipopolissacarídeo), que estão presentes em bactérias gram-negativas, são agentes causadores de lesões periapicais. E tem capacidade de penetrar os corantes fotossensibilizadores no interior dos túbulos dentinários infectados (Matsushima et al 2021).…”
Section: Revisão De Literaturaunclassified
“…[334][335][336] Therefore, PDT can not only be used for dental bacteria inactivation. [337,338] and wound healing in dentistry, [339] more importantly, it can provide the dawn of cure for patients with MDR bacteria infection.…”
Section: Combat Microbial Infection and Resistancementioning
confidence: 99%